Madrasah Strategy in Strengthening Digital Literacy Skills for Students of MTSN 1 Pidie Jaya - Nurlina; Dhiauddin; Saifuddin (PT. Anagata Sembagi Education, 2025)
The main problem faced in literacy among students is low interest in reading, which is triggered by limited access to interesting books, distractions from social media, and less motivating teaching methods. In addition, writing and speaking skills are also obstacles, because many students have difficulty in developing these skills due to lack of practice, minimal understanding of grammar, and limited support. This study aims to explore the strategies implemented by MTsN 1 Pidie Jaya in supporting digital literacy, including the integration of digital literacy into the curriculum and digital literacy development programs for students. The research method used is qualitative with data collection techniques through observation, interviews, and document analysis. The results of the study show that MTsN 1 Pidie Jaya has succeeded in improving students' digital literacy through a strategy of integrating technology into the curriculum, providing access to devices, and teacher training that focuses on cybersecurity, digital ethics, and practical skills. This school is committed to continuing to improve students' digital literacy through interactive training programs and learning innovations, while addressing infrastructure and access challenges through effective collaboration. In addition, MTsN 1 Pidie Jaya also implements various effective programs to improve students' digital literacy, including special training, project-based learning approaches, gamification, and continuous evaluation.